Upaya Meningkatkan Hasil Belajar Pembelajaran Tari Piring Tradisi melalui Metode Drill di Kelas XI. F6 SMA N 14 Padang - Marchel, Qonita Hesthia; Syeilendra, Syeilendra (Lembaga Yasin AlSys, 2024)
The purpose of this study is to know the improvement of learning outcomes of the ancient Piring dance with the experimental method in class XI. F6 SMA N 14 Padang. This type of research is group action research or